Versatile one-pot synthesis of gold nanoclusters and nanoparticles using 3, 6-(dipyridin-2-yl)-(1, 2, 4, 5)-tetrazine. Issue 12 (10th February 2021) - Rus, Yahdi Bin; Bosmi, Margarita; Maisonneuve, Stéphane; Guérineau, Vincent; Noël, Vincent; Courty, Alexa; Miomandre, Fabien
Abstract : Easy synthesis of gold nanoclusters stabilized by thiols and tetrazines. Abstract : A one-pot synthesis of gold nano-objects is described by simply mixing a gold salt (HAuCl4 ), dodecanethiol and 3, 6-di-2-pyridyl-1, 2, 4, 5-tetrazine. When a large excess of thiol is used, gold nanoclusters of 2 nm are obtained in a large amount and with a narrow size distribution. The reaction mechanism was investigated by absorption and emission spectroscopies and shows the in situ formation of dihydrotetrazine acting as the reductant of Au(iii ) to make Au(0). Au nanoclusters were isolated from the molecular precursors by HPLC. The nature of the ligands stabilizing Au nanoclusters was investigated by various techniques such as mass spectrometry, SEM-EDS, XPS and NMR. Thiol and tetrazine are shown to play both the role of ligand stabilizing the clusters. Finally, when a much smaller amount of thiol is used, a mixture of Au nanoclusters and Au nanoparticles of 10–15 nm, sometimes aggregated into clusters of 50 nm is obtained. The formation of larger nanoobjects is explained by the lower amount of thiol available to block the growth at the early stage as shown by UV-vis absorption monitoring.